Military lexics in the novel „Malwy” by R. Ivanychuk - Дубинець, Зореслава Олександрівна (The Journal of V. N. Karazin Kharkiv National University. Series “Philology”)
The article deals with the problem of the issue of military lexics of the Ukrainian language and and analyzed the names of persons related to military affairs in the Ukrainian language, especially in literature, for example, in the historical novel „Malwy” by R. Ivanychuk. It examines groups military tokens based on their semantics presented information about their origin and fate. The author uses some of the words etymology has not been established. The writer reveals knowledge not only with the common names of soldiers, military ranks , positions and ranks of the Cossacks, but the semantics and origin of the name of representatives of the Turkish and Polish army.